The role of metal ion metabolism in the pathogenesis of diabetes and associated complications - Liu, Siyuan; Chen, Xuzhuo; Qi, Xinrui; Bai, Jiahao; Tong, Bin; Zhang, Deju; Yin, Xiaoping; Yu, Peng (Frontiers in Endocrinology, 2025)
Diabetes is a growing health concern, accompanied by significant complications like cardiovascular disease, kidney disease, and retinopathy. Metal ions, including iron, zinc, and copper, play a crucial role in maintaining human health through their balance within the body. Disruptions in metal ion balance can intensify diabetic conditions. For instance, iron overload induces oxidative stress, which harms islet β cells and impacts vascular complications of diabetes. Abnormal copper levels heighten insulin resistance, and zinc deficiency has a strong connection with type 1 diabetes. Future in - depth exploration of the association between metal metabolism and diabetes holds the potential to uncover novel treatment avenues, enhancing both the quality of life and health prognosis for patients.